2020
DOI: 10.3390/md18120648
|View full text |Cite
|
Sign up to set email alerts
|

The Reducing Effects of Pyrogallol-Phloroglucinol-6,6-Bieckol on High-Fat Diet-Induced Pyroptosis in Endothelial and Vascular Smooth Muscle Cells of Mice Aortas

Abstract: In hyperlipidemia, pyroptosis in endothelial cells (ECs) induces atherosclerosis via the toll-like receptor 4 (TLR4) pathway. We evaluated the effects of Ecklonia cava extract (ECE) and pyrogallol-phloroglucinol-6,6-bieckol (PPB) on pyroptosis of ECs and vascular smooth muscle cells (VSMCs), which leads to attenuation of these cells and dysfunction of the aorta in high-fat-diet (HFD)-fed mice and in palmitate-treated ECs and VSMCs. The expression of TLR4 and nuclear factor kappa-light-chain-enhancer of activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…PI staining results showed that BAY pretreatment also reduced the proportion of dead cells ( Zhaolin et al, 2019 ). Correspondingly, studies showed that melatonin and PPB alleviate atherosclerosis in HFD-fed ApoE −/− mice via inhibiting NF-κB-mediated pyroptosis in ECs( Schmitz and Ruebsaamen, 2010 ; Oh et al, 2020 ). It is well known that mitochondrial damage and reactive oxygen species (ROS) production are sufficient to activate NF-κB signal ( Morgan and Liu, 2011 ; Formentini et al, 2012 ).…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…PI staining results showed that BAY pretreatment also reduced the proportion of dead cells ( Zhaolin et al, 2019 ). Correspondingly, studies showed that melatonin and PPB alleviate atherosclerosis in HFD-fed ApoE −/− mice via inhibiting NF-κB-mediated pyroptosis in ECs( Schmitz and Ruebsaamen, 2010 ; Oh et al, 2020 ). It is well known that mitochondrial damage and reactive oxygen species (ROS) production are sufficient to activate NF-κB signal ( Morgan and Liu, 2011 ; Formentini et al, 2012 ).…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…On the other hand, existing studies have indicated that multiple drugs and genes such as melatonin, salidroside (SAL), estrogen, pyrogallol-phloroglucinol-6,6-bieckol (PPB) and fibroblast growth factor 21 (FGF21) decrease atherosclerosis plaque formation via inhibiting ECs pyroptosis in vivo and in vitro ( Zhang et al, 2018 ; Oh et al, 2020 ; Xing et al, 2020 ; Zeng et al, 2020 ; Meng et al, 2021 ). Moreover, recent studis have discovered more drugs and miRNAs that could regulate ECs pyroptosis, including atorvastatin, miRNA-30c-5p, miRNA-125a-5p, etc.…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…Xianxian Wu et al ( Wu et al, 2018 ) proved that nicotine induces atherosclerosis by stimulating the production of ROS to activate the classic pyroptosis pathway of caspase-1-dependent endothelial cells. In addition to nicotine, hyperlipidaemia, proinflammatory factors and many other factors are all induced by activating the caspase-1-sirtuin1-activator protein-1 pathway ( Yin et al, 2015 ; Oh et al, 2020 ). This also suggests that we can treat certain cardiovascular diseases by preventing the activation of caspase-1.…”
Section: Mitochondrial and Systemic Diseasesmentioning
confidence: 99%
“…Oh et al found that Pyrogallol-Phloroglucinol-6,6-Bieckol (PPB) significantly hindered monocyte migration and macrophage differentiation towards the inflammatory phenotype ( Oh et al, 2018 ). Thus, PPB reduces monocyte-induced EC death and monocyte-induced VSMC proliferation and migration, and the effect of PPB on pyroptosis (leading to attenuation of these cells and aortic cell dysfunction) of endothelial cells and VSMCs in high-fat diet (HFD)-fed mice ( Oh et al, 2020 ). In a high glyceride, high cholesterol environment, SIRT1 expression is suppressed, leading to reduced reverse cholesterol transport, mediating the differentiation of monocytes to foam cells and impeding the reduction of foam cells in atherosclerotic plaques ( Kitada et al, 2016 ).…”
Section: The Molecular Pathways Of Pyroptosis In Atherosclerosismentioning
confidence: 99%